A quantitative analysis of electronic transport in n- and p-type modulation-doped GaAsBi/AlGaAs quantum well structures. (20th October 2021) - Donmez, Omer; Erol, Ayse; Çetinkaya, Çağlar; Çokduygulular, Erman; Ayd𝚤n, Mustafa; Y𝚤ld𝚤r𝚤m, Saffettin; Puustinen, Janne; Hilska, Joonas; Guina, Mircea
Abstract: Electronic transport properties of as-grown and thermally annealed n- and p-type modulation-doped GaAsBi/AlGaAs quantum well (QW) structures were investigated. Hall mobility of as-grown, n- and p-type modulation doped QW structures are found from raw experimental data as ∼1414 and 95 cm 2 Vs −1 at room temperature. A comparison between reported two-dimensional (2D) electron density determined from the analyses of Shubnikov de Haas oscillations and the 2D Hall electron density indicates a presence of parallel conduction in barrier layer (AlGaAs) and QW layer (GaAsBi) in n-type samples, therefore a parallel channel conduction theory is used to separate the electron mobility in the QW and the barrier layers in n-type modulation doped GaAsBi/AlGaAs QW structure. The extracted electron mobility of the as-grown n-type GaAsBi/AlGaAs QW sample is determined as ∼5975 cm 2 Vs −1 at 4.2 K, which is closer to the electron mobility in GaAs. It is found that thermal annealing at lower temperature than growth temperature increases electron mobility of 2D electron gas, while annealing at higher temperature than growth temperature decreases electron mobility. The temperature dependence of the extracted electron mobility using parallel conduction approximation is analytically calculated by considering possible scattering mechanisms. Analysis of temperature-dependent electron mobility shows that the dominant scattering mechanisms are interface roughness (IFR), acoustic, and alloy-potential scatterings at low and intermediate temperature range, and IFR and optical phonon scattering at the high-temperature range in n-type modulation doped GaAsBi/AlGaAs QW structures.